Leading highly performing children's centres: Supporting the development of the 'accidental leaders'. (September 2016) - Coleman, Andy; Sharp, Caroline; Handscomb, Graham
There is wide recognition that early childhood experiences are critical to a child's development and their subsequent life chances. However, little research has been undertaken into leadership in early years settings, which is so influential in this regard. This article summarizes research into the leadership of Sure Start Children's Centres, which provide support to the most vulnerable children and families. Completed by the National Foundation for Educational Research (NFER) on behalf of NCSL, this research involved a review of literature on early years leadership and the production of 25 case studies of leaders of 'highly effective' children's centres. The study identified three specific challenges faced by leaders of children's centres. Two of these, ensuring positive outcomes for children and dealing with change, are particularly salient in light of challenges affecting leaders in times of austerity. The third, increasing the visibility and value of leadership, is a perennial challenge for the sector. The study found that leaders demonstrated eight core behaviours to address these challenges. These included engaging responsively with families, using evidence to drive improvement, motivating and empowering staff and embracing integrated working. The authors recommend that these behaviours inform the delivery of future leadership development for these leaders.